¿ Y el pluralismo teórico? - Cepeda, Margarita (2005)
The paper deals with the problem of theorelical pluralism, in the light of Dr. Hamer's case. founder of the New Medicine. After questioning the relationship between justice and pluralism as conceived of by contemporary politica liberalism, the paper defends an alternative of a hermeneutical type akin to Geertz's position versus Rorty's. which would counterbalance the typical reactionary position of every form of established knowledge.